Paleosols record dry and humid paleoenvironments during the Upper Pleistocene in the Brazilian Pantanal - Ladeira, Francisco Sérgio Bernardes; Mescolotti, Patricia Colombo [UNESP]; do Nascimento Pupim, Fabiano; de Faria, Laura Milani Dias Mathias; Assine, Mario Luis [UNESP] (Elsevier, 2022)
Information on Quaternary landscapes and paleoenvironmental changes in the interior of Brazil are scarce. One of such areas, particularly sensitive to these variations, is the modern tropical Pantanal wetland, whose alluvial deposits record paleoenvironmental and paleoclimatic changes during the late Quaternary. Based on detailed pedological and sedimentological descriptions, stimulated optical luminescence dating and analytical data we described a well-exposed sedimentary succession that crops out in slope terraces of the Aquidauana River, located in the southern area of the Pantanal. We interpret environmental changes that have occurred since the beginning of the Upper Pleistocene, and which affected sedimentation and biogeochemical processes. Basal deposits comprise cross-stratified sands, which record active fluvial sedimentation from ∼106 to ∼70 ka, a period of probable increased river discharge. Fluvial channel facies are overlaid by pedogeneized floodplain deposits, in which we recognized a pedocomplex composed of a sequence of three late Pleistocene truncated paleosol profiles and a Holocene soil profile. The two lower paleosols are Vertisols with mottling, slickensides, rhizolites and septarian glaebules of carbonate. These characteristics indicate prolonged drought periods under semi-arid to arid climates ca. ∼70 and ∼30 ka. The upper paleosol profile is a Planosol (Ultisol) with block structure, waxiness, iron glaebules, and manganese films, pointing to prevailing humid climates during the terminal Pleistocene (since ∼30 ka). Covering this truncated Planosol is a layer of fine to medium-grained Holocene sands, with development of a horizon A of an Arenosol (Entisol). These paleoenvironmental changes correlate with regional changes in precipitation deduced from speleothems in nearby plateaus and in southeastern Brazilian sites.
Keywords: Optically stimulated luminescence (OSL); Paleoclimate; Pedocomplex